Continued-fractions representations of the functions sh z, ch z, sin z, cos z - Pahirya, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain the representations of the functions sh z, ch z, sin z, and cos z by quasireciprocal functional continued fractions of the Thiele type.